2010
DOI: 10.1002/14651858.cd007046.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Duration of adjuvant chemotherapy for patients with non-metastatic colorectal cancer

Abstract: The present meta-analysis confirmed that adjuvant chemotherapy of CRC should not last for more than 6 months. Prolonged duration would result in lower benefit to risk ratio. However, the results do not make it possible to favour either 3 or 6 month durations. They should help design a future RCT comparing different durations of continuous treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 10 publications
1
39
0
1
Order By: Relevance
“…Current recommendations are for patients with high-risk stage Ⅱ and stage Ⅲ CRC to receive 6 mo of adjuvant chemotherapy after primary surgical resection, and for patients with low-risk stage Ⅱ CRC to be considered for adjuvant chemotherapy, enrolled in a clinical trial or observed without adjuvant therapy [77,79] . The specific chemotherapeutic regimens have been reviewed recently in detail [77,80] .…”
Section: Adjuvant Therapy and Surveillancementioning
confidence: 99%
“…Current recommendations are for patients with high-risk stage Ⅱ and stage Ⅲ CRC to receive 6 mo of adjuvant chemotherapy after primary surgical resection, and for patients with low-risk stage Ⅱ CRC to be considered for adjuvant chemotherapy, enrolled in a clinical trial or observed without adjuvant therapy [77,79] . The specific chemotherapeutic regimens have been reviewed recently in detail [77,80] .…”
Section: Adjuvant Therapy and Surveillancementioning
confidence: 99%
“…Mediante colectomía y resección en bloque de ganglios locorregionales, en paciente sin metástasis, una cirugía completa puede ser curativa 6 . Los pacientes con enfermedad etapa clínica I no requieren terapia adyuvante 7 8 . Del 60% de los pacientes con CCR que presentarán metástasis, un 80% tienen enfermedad hepática irresecable; la enfermedad hepática es la causa más frecuente de muerte en estos pacientes.…”
Section: Introductionunclassified
“…For patients with clinical Stage III disease, 6-month chemotherapy is recommended, and they can receive FOL-FOX or CapeOx; FLOX, or capecitabine monotherapy or 5-fluorouracyl/leucovorin in those in whom oxaliplatin is contraindicated 8 . Out of 60% of CRC patients that will develop metastasis, 80% will develop unresectable liver disease, with liver disease being the most common cause of death in these patients.…”
Section: Introductionmentioning
confidence: 99%